Creativity under workload pressure and integrative complexity: The double-edged sword of paradoxical leadership - Shao, Yan; Nijstad, Bernard A.; Täuber, Susanne (Organizational behavior and human decision processes, 2019)
•Paradoxical leader behavior (PLB) may fuel creativity in demanding situations.•Workload pressure and integrative complexity moderate the PLB-creativity link.•Effects of PLB on creativity are positive only when both moderators are high.•The effects are negative when workload is high and integrative complexity is low.•Creative self-efficacy mediates the three-way interaction effect on creativity. Modern-day organizations often demand creativity, but motivating creativity under unfavorable conditions such as high workload pressure is difficult. Integrating paradox theory and social cognitive theory, we conceptualize creativity as a process that involves tensions among competing goals and demands, and those tensions become salient under high workload pressure. We propose that learning to constructively deal with such salient tensions is important for the development of creativity and that paradoxical leader behavior (PLB) may stimulate creativity by enhancing employees’ creative self-efficacy (CSE) in such challenging situations. However, PLB will only promote CSE and employee creativity when employees have a high level of integrative complexity to accept and appreciate the complex and paradoxical behaviors of the leader. Based on data from 252 employee-supervisor dyads, we found that through CSE, PLB was most effective in promoting employee creativity when workload pressure and integrative complexity were both high. However, PLB was less effective for promoting CSE and creativity when workload pressure was low, or when workload pressure was high while integrative complexity was low. Implications and limitations of our research are discussed.